2011
DOI: 10.1002/term.485
|View full text |Cite
|
Sign up to set email alerts
|

Flux of selected body fluid constituents and benzylpenicillin in polyacrylamide hydrogel (PAAG)

Abstract: The polyacrylamide hydrogel (PAAG) Aquamid® (Contura International A/S Soeborg, Denmark) is one of the new macromolecules that are used as implants and tissue fillers in reconstruction and aesthetic surgery. This study showed, by means of radioactive isotope methods, that PAAG can exchange both physiological and non-physiological constituents very efficiently with the surrounding medium. The efflux (J, mole/(cm(2)× s), 25 °C, pH 7.2) of water (4.4 × 10(-5) ), chloride (2.4 × 10(-7) ), urea (1.0 × 10(-9) ), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Even high successive doses of tobramycin and rifampicin failed to eradicate the bacteria harbored in the gel, in spite of the administration of 100 times the MIC value once a day for 7 days. The PAAG has demonstrated host vessel ingrowth in an porcine model (Christensen et al ., ), and it has been shown that this hydrogel is capable of exchanging physiological and nonphysiological constituents like benzylpenicillin very efficiently with the surrounding medium (Brahm et al ., ). This means that the antibiotics had full access to the bacteria and that their protection against these antibiotics was most likely explained by the enhanced biofilm mode of growth, which we observed in the microscope (Figs and ).…”
Section: Discussionmentioning
confidence: 97%
“…Even high successive doses of tobramycin and rifampicin failed to eradicate the bacteria harbored in the gel, in spite of the administration of 100 times the MIC value once a day for 7 days. The PAAG has demonstrated host vessel ingrowth in an porcine model (Christensen et al ., ), and it has been shown that this hydrogel is capable of exchanging physiological and nonphysiological constituents like benzylpenicillin very efficiently with the surrounding medium (Brahm et al ., ). This means that the antibiotics had full access to the bacteria and that their protection against these antibiotics was most likely explained by the enhanced biofilm mode of growth, which we observed in the microscope (Figs and ).…”
Section: Discussionmentioning
confidence: 97%
“…PAAG is mainly composed of 2.5% polymerized (cross-linked) polyacrylamide in non-pyrogenic water [17] . The high water content of PAAG allows the material to assimilate into the connective tissues of the mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Polyacrylamide gel is a synthetic non-degradable, biocompatible and non-toxic substance with waterexchanging abilities (Zarini et al, 2004;and Brahm et al, 2012). It is a relatively recent addition to the clinician's options when considering treatments for OA.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%